Anti-Inflammatory Effects of RTD-1 in a Murine Model of Chronic Pseudomonas aeruginosa Lung Infection: Inhibition of NF-κB, Inflammasome Gene Expression, and Pro-IL-1β Biosynthesis - Mansour A. Dughbaj; Jordanna G. Jayne; A Young J. Park; Timothy J. Bensman; Marquerita Algorri; Andre J. Ouellette; Michael E. Selsted; Paul M. Beringer (MDPI AG, 2021)
Vicious cycles of chronic airway obstruction, lung infections with Pseudomonas aeruginosa, and neutrophil-dominated inflammation contribute to morbidity and mortality in cystic fibrosis (CF) patients. Rhesus theta defensin-1 (RTD-1) is an antimicrobial macrocyclic peptide with immunomodulatory properties. Our objective was to investigate the anti-inflammatory effect of RTD-1 in a murine model of chronic P. aeruginosa lung infection. Mice received nebulized RTD-1 daily for 6 days. Bacterial burden, leukocyte counts, and cytokine concentrations were evaluated. Microarray analysis was performed on bronchoalveolar lavage fluid (BALF) cells and lung tissue homogenates. In vitro effects of RTD-1 in THP-1 cells were assessed using quantitative reverse transcription PCR, enzyme-linked immunosorbent assays, immunoblots, confocal microscopy, enzymatic activity assays, and NF-κB-reporter assays. RTD-1 significantly reduced lung white blood cell counts on days 3 (−54.95%; p = 0.0003) and 7 (−31.71%; p = 0.0097). Microarray analysis of lung tissue homogenates and BALF cells revealed that RTD-1 significantly reduced proinflammatory gene expression, particularly inflammasome-related genes (nod-like receptor protein 3, Mediterranean fever gene, interleukin (IL)-1α, and IL-1β) relative to the control. In vitro studies demonstrated NF-κB activation was reduced two-fold (p ≤ 0.0001) by RTD-1 treatment. Immunoblots revealed that RTD-1 treatment inhibited proIL-1β biosynthesis. Additionally, RTD-1 treatment was associated with a reduction in caspase-1 activation (FC = −1.79; p = 0.0052). RTD-1 exhibited potent anti-inflammatory activity in chronically infected mice. Importantly, RTD-1 inhibits inflammasome activity, which is possibly a downstream effect of NF-κB modulation. These findings support that this immunomodulatory peptide may be a promising therapeutic for CF-associated lung disease.